2023
DOI: 10.1039/d2cp03841b
|View full text |Cite|
|
Sign up to set email alerts
|

Helium nanodroplets as an efficient tool to investigate hydrogen attachment to alkali cations

Abstract: We report a novel method to reversibly attach and detach hydrogen molecules to positively charged sodium clusters formed inside a helium nanodroplet host matrix. It is based in the controlled...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 59 publications
3
10
1
Order By: Relevance
“…(H 2 ) n Na + clusters have been recently investigated by some of us and other coworkers in a joint experimental-computational work. [26] Cluster populations, measured by a mass spectrometer after formation inside a helium nanodroplet, showed peaks revealing specially stable cluster sizes, in agreement with the calculations. The work is here extended with the application of the Ad-PsAt model to both p/oH 2 isomers.…”
Section: Introductionsupporting
confidence: 85%
See 2 more Smart Citations
“…(H 2 ) n Na + clusters have been recently investigated by some of us and other coworkers in a joint experimental-computational work. [26] Cluster populations, measured by a mass spectrometer after formation inside a helium nanodroplet, showed peaks revealing specially stable cluster sizes, in agreement with the calculations. The work is here extended with the application of the Ad-PsAt model to both p/oH 2 isomers.…”
Section: Introductionsupporting
confidence: 85%
“…[38] It can be seen that the evaporation energies of the Na + -doped clusters (upper panel) decrease with n already for the smallest clusters, despite having rather large values. This is due to the role of the (repulsive) 3B interaction as well as the increasing repulsion among the hydrogen molecules when their number increases [26] or, in other words, the packing difficulties of molecules surrounding the ion with a "helicopter motion". Nevertheless, clusters with six and eight H 2 molecules show a special stability with respect to neighboring sizes and indeed it has been experimentally found that they are more abundant.…”
Section: Results and Discussion: Cluster Energies And Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…7) strongly reduces down to about 60 meV, that is in the same energy range previously observed for the adsorption on alkali ions, where typical non covalent interactions dominate. 46,47 Similar considerations also apply to the (H 2 ) k HCu + clusters whose structures show symmetries which could arise from different hybridization of the Cu + orbitals: in this case the pattern as a function of k is different (due the presence of a Cu–H chemical bond) and for k = 4 a geometry similar to that for a dsp 3 -like hybridization of the metal can be also appreciated (see Fig. 2).…”
Section: Resultsmentioning
confidence: 74%
“…50,51 The Cu n + (n = 1-8) doped HNDs are guided by an RF-hexapole (EVAP) filled with H 2 gas, as it was also done previously for alkali cations. 47 In the EVAP chamber He from the HNDs evaporates due to the high number of collisions with room temperature H 2 (99.999%, Messer). Additionally, the Cu clusters react with H 2 and exothermic processes also lead to He evaporation from the HND.…”
Section: Methodsmentioning
confidence: 99%